Did the Taconic Appalachians continue into southern South America - Dalla Salda, Luis Hugo (1992)
The Appalachian Mountains, now terminating abruptly at the Gulf of Mexico coastal plain, may have formerly continued into southern South America. Rocks forming the basement of the Argentine Andes can be interpreted as remnants of an early Paleozoic orogen, the Famatinian belt, not unlike the Taconic Appalachians. Both orogens are bordered to the west (present coordinates) by lower Paleozoic carbonate platforms bearing the Olenellid trilobite fauna that is characteristic of Laurentia. Paleomagnetic and geologic data indicate that they could have formed as one continuous mountain chain, possibly extending into Antarctica, during Ordovician closure of an ocean basin ("southern" Iapetus) between Laurentia and Gondwana. The Taconic and Famatinian segments of the chain may have been truncated during Late Ordovician separation of Laurentia and Gondwana along the preexisting (late Neoproterozoic to Cambrian) rift system that initiated formation of the Ouachita embayment and the southern margin of North America.